2014
DOI: 10.1002/2014gl059380
|View full text |Cite
|
Sign up to set email alerts
|

Uplift and subsidence reveal a nonpersistent megathrust rupture boundary (Sitkinak Island, Alaska)

Abstract: We report stratigraphic evidence of land-level change and tsunami inundation along the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 32 publications
3
74
0
Order By: Relevance
“…On the south coast of Sitkinak Island, only 125 km east of Chirikof Island, Briggs et al (2014a) identified uplift and subsidence during 5 great earthquakes and 6 possible tsunami beds dating from the past 3000 yr. The youngest of the beds, probably deposited by the 1788 tsunami, can be traced continuously 1.3 km inland.…”
Section: Tsunami Recurrencementioning
confidence: 98%
See 4 more Smart Citations
“…On the south coast of Sitkinak Island, only 125 km east of Chirikof Island, Briggs et al (2014a) identified uplift and subsidence during 5 great earthquakes and 6 possible tsunami beds dating from the past 3000 yr. The youngest of the beds, probably deposited by the 1788 tsunami, can be traced continuously 1.3 km inland.…”
Section: Tsunami Recurrencementioning
confidence: 98%
“…11). Bed correlations at the Drained Lake site show that bed D rises higher than the beds of other probable tsunami deposits, reaching almost 15 m ( (Lander, 1996;Briggs et al, 2014a).…”
Section: Historical Tsunamismentioning
confidence: 99%
See 3 more Smart Citations